Mother's Anxiety Face Primigravidal Delivery Ages 20-35 Years at Mandiri Midwife Practices Cengkal Sewu Village, Kayen District, Pati Regency - Lestari, Nur Cahyani Ari; Sumiati, Sumiati (Akademi Keperawatan RSPAD Gatot Soebroto, 2021)
Anxiety before labor in pregnant women is a physiological matter, but in facing labor process in which there are a series of physical and psychological changes that starting with uterine contractions, dilatation of the birth canal, and spending baby and placenta which ended with first punding between mother and baby. Anxiety and depression are two types of interference that related each other. The objectives of this study is to explore mother’s anxiety facing labor primigravid 20-35 years old in BPM Sulityowati Cengkalsewu Village Sub Kayen Pati Regency. This study used a qualitative method with phenomenological approach. Technique of data collection with in depth interview and purposive sampling. The results of in-depth interview in participant obtained information mother’s anxiety resolve labor primigravid 20-35 years old about definition, causes, family support, factors of anxiet. and how to prevent and resolve anxiety. All mothers who are facing labor already know about the content of the anxiety in the face of first child labor. As well as how to prevent and resolve that anxiety.Mother’s anxiety facing labor primigravid 20-35 years old is good.